Preparation and characteristics of lipid nanoemulsion formulations loaded with doxorubicin - Jiang, Sai-Ping (Dove Medical Press, 2013)
PURPOSE: Safe and effective lipid nanoemulsion (LNE) formulations for the antitumor delivery of doxorubicin is designed. METHODS: LNEs composed of medium-chain triglyceride, soybean oil, lecithin, and doxorubicin are prepared by a solvent-diffusion method in an aqueous system. The effects of lipid material composition and polyethylene glycol (PEG)ylation on the size, drug encapsulation efficiency, and stability of LNEs are investigated. Based on in-vitro cytotoxicity and cellular uptake tests of A549 (human lung carcinoma) cells, in-vivo biodistribution, antitumor activity, and cardiac toxicity are further examined using nude mouse bearing A549 tumor. RESULTS: The LNE size decreases from 126.4 ± 8.7 nm to 44.5 ± 9.3 nm with increased weight ratio of medium-chain triglyceride to soybean oil from 1:4 to 3:2, whereas the encapsulation efficiency of doxorubicin is slightly reduced from 79.2% ± 2.1% to 71.2% ± 2.9%. The PEGylation of LNE by 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[carboxy(PEG)2000] (DSPE-PEG 2000) does not significantly change the size and drug encapsulation efficiency. Three-month storage at room temperature and lyophilization process does not affect the drug encapsulation efficiency, whereas the size slightly increases to almost 100 nm. The in-vitro drug-release profiles of LNEs suggest that the present formulation can prolong drug release for 48 hours. LNEs can be internalized into tumor cells in vitro and efficiently accumulate in tumor tissues in vivo by passive targeting. Analysis results of in-vitro and in-vivo antitumor activities reveal that doxorubicin-loaded LNE exerts a therapeutic effect similar to that of the commercial Adriamycin. Moreover, the toxicity of doxorubicin, particularly its cardiac toxicity, is reduced. CONCLUSION: The present LNE formulation of doxorubicin can effectively suppress tumor growth and improve the safety of Adriamycin.